2016
DOI: 10.1038/nature18637
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive transcriptional map of primate brain development

Abstract: The transcriptional underpinnings of brain development remain poorly understood, particularly in humans and closely related non-human primates. We describe a high resolution transcriptional atlas of rhesus monkey brain development that combines dense temporal sampling of prenatal and postnatal periods with fine anatomical parcellation of cortical and subcortical regions associated with human neuropsychiatric disease. Gene expression changes more rapidly before birth, both in progenitor cells and maturing neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
348
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 351 publications
(365 citation statements)
references
References 80 publications
17
348
0
Order By: Relevance
“…Between D100 and D125 in vitro, the rate of transcriptomic changes appeared to slow. A slow-down in gene expression dynamics has been observed in previous studies of human cortical development (Bakken et al, 2016;Colantuoni et al, 2011). It is possible that our in vitro observations reflect similar changes occurring at equivalent ages in vivo, or that some extrinsic element necessary for continued development of these cells is missing from our protocol, as previous work has suggested that development is comparatively slow in vitro (Sadegh and Macklis, 2014).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Between D100 and D125 in vitro, the rate of transcriptomic changes appeared to slow. A slow-down in gene expression dynamics has been observed in previous studies of human cortical development (Bakken et al, 2016;Colantuoni et al, 2011). It is possible that our in vitro observations reflect similar changes occurring at equivalent ages in vivo, or that some extrinsic element necessary for continued development of these cells is missing from our protocol, as previous work has suggested that development is comparatively slow in vitro (Sadegh and Macklis, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…more mature) pseudotime neurons ( Figure 3B, right panels). To verify these results, we compared gene expression changes correlated with pseudotime for our in vitro cells to gene expression patterns observed in the developing non-human primate and human brains ( Figure S6) (Bakken et al, 2016). We find that genes positively or negatively correlated with pseudotime in vitro are expressed in similar patterns in vivo.…”
Section: Scrna-seq Analysis Of In Vitro-derived Human Interneuronsmentioning
confidence: 77%
“…To date, many studies have shown the heterogeneity of neural precursor cells (Johnson et al 2015;Llorens-Bobadilla et al 2015) and neurons (Molyneaux et al 2007;Pollen et al 2014;Darmanis et al 2015;Usoskin et al 2015) in mouse and human brain by scRNA-seq. However, due to complexity of data analysis of cellular dynamics, coupled with the biological variability (birth, death, and differentiation) of individual cells, as well as the presence of technical, environmental, and intracellular noise (Kuznetsov 2001(Kuznetsov , 2003Kuznetsov et al 2002;Kim and Marioni 2013;Kharchenko et al 2014;Buettner et al 2015;Daigle et al 2015;Vu et al 2016), it remains a challenge to interpret the heterogeneity and dynamics of NPC to neuron transitions (Camp et al 2015;Bakken et al 2016;Yao et al 2017). Given the lack of synchronous development, the molecular patterns that switch on and switch off pathways governing alternative neuronal fate choices (Ming and Song 2011) are not clear.…”
mentioning
confidence: 99%
“…3 H]dT in macaque monkeys at various gestational ages to label the cohorts of neurons that were born at that period to establish the inside-first, outside-last generation of cortical layers in primates and produce fundamental insights into the timing of the generation of the macaque cortical neuronal cohorts that we still use today (7). Since then we gained a much better understanding of the subplate and its dynamic interactions with incoming afferents and forming cortical circuits in a variety of species (4, [8][9][10][11].…”
mentioning
confidence: 99%
“…Since then we gained a much better understanding of the subplate and its dynamic interactions with incoming afferents and forming cortical circuits in a variety of species (4, [8][9][10][11]. Additionally, the subplate has been the subject of imaging studies and transcriptomic analyses because of increasing evidence for its association with various cognitive developmental disorders (7,(12)(13)(14).…”
mentioning
confidence: 99%